RESPONS SISWA TERHADAP PRAKTIKUM PEMBUATAN CAKE PEPAYA PADA SUBMATERI PERAN TUMBUHAN DI BIDANG EKONOMI - Qamariah, Widya; Daningsih, Entin; Yokheb, Yokheb (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis aim of this study was to know the students response to making papaya cake laboratory work on subchapter role of plant in economy class X high school. This research used descriptive methods. Cake making laboratory work to show subchapter role of plant in economy material and than to process papaya become cake. Stop motion animation was used on papaya cake making laboratory work of grade X students MIPA 4 MAN 2 Pontianak. This Laboratory work used questionnaire to know students responses. Questionnaire responses consisted of 12 statements, 8 positive statements and 4 negative statements. The results of questionnaires response was analyzed using likert scale. The results of questionnaires response was very high category with a percentage of 87.01%. In addition, the results of the laboratory work reached 100% completeness with minimum completeness criteria 78 and the average grade cognitive value of 88.03, affective of 92.92 and psychomotor of 90.17.Keyword: Laboratory work, Respons, Questionnaire